The Correlation Between Vocabulary And Reading Comprehension Of SMA Negeri 3 Palu Students - Indah Farawansa Moh.S.Mahid; Anjar Kusuma Dewi; Maghfira Maghfira; Afrillia Anggreni (Hasanuddin University, 2025)
Vocabulary can be defined as the list of words in a language that are understood and memorized, playing an important role in communication and learning processes, while reading comprehension is the ability to understand, interpret, and evaluate the meaning of written texts. This study aims to investigate the correlation between vocabulary and reading comprehension at SMA Negeri 3 Palu. The method used was correlational research, employing vocabulary tests and reading comprehension tests as data collection instruments. The sample consisted of 36 students selected through purposive sampling. The collected data were analyzed using the Pearson Product Moment correlation technique. The results showed a significant positive correlation between vocabulary and reading comprehension ability at SMA Negeri 3 Palu. These findings indicate that an increase in vocabulary can improve reading comprehension.